NORs on human acrocentric chromosome p-arms are active by default and can associate with nucleoli independently of rDNA - van Sluis, Marjolein (Proc Natl Acad Sci U S A, 2020)
Nucleoli, the sites of ribosome biogenesis and the largest structures in human nuclei, form around nucleolar organizer regions (NORs) comprising ribosomal DNA (rDNA) arrays. NORs are located on the p-arms of the five human acrocentric chromosomes. Defining the rules of engagement between these p-arms and nucleoli takes on added significance as describing the three-dimensional organization of the human genome represents a major research goal. Here we used fluorescent in situ hybridization (FISH) and immuno-FISH on metaphase chromosomes from karyotypically normal primary and hTERT-immortalized human cell lines to catalog NORs in terms of their relative rDNA content and activity status. We demonstrate that a proportion of acrocentric p-arms in cell lines and from normal human donors have no detectable rDNA. Surprisingly, we found that all NORs with detectable rDNA are active, as defined by upstream binding factor loading. We determined the nucleolar association status of all NORs during interphase, and found that nucleolar association of acrocentric p-arms can occur independently of rDNA content, suggesting that sequences elsewhere on these chromosome arms drive nucleolar association. In established cancer lines, we characterize a variety of chromosomal rearrangements involving acrocentric p-arms and observe silent, rDNA-containing NORs that are dissociated from nucleoli. In conclusion, our findings indicate that within human nuclei, positioning of all 10 acrocentric chromosomes is dictated by nucleolar association. Furthermore, these nucleolar associations are buffered against interindividual variation in the distribution of rDNA.